Familiarization of dentists with the problems of temporomandibular disorders on the example of the Lviv region of Ukraine - Semchyshyn Я. О.; Shybinska М. В. (Actual Dentistry, 2024)
The aim of the study is to assess the awareness of dentists with the problems of temporomandibular disorders on the example of the Lviv region of Ukraine and determine the need to improve their training on these issues. Materials and methods. Using a specially designed questionnaire, 80 dentists were interviewed about their awareness of the problems of temporomandibular disorders. The results are statistically processed. Research results. The answers to the questionnaire questions indicate that dentists ‘ views on possible factors and methods of treating patients with TMD are different. It was found that 67.5% of dentists surveyed did not receive TMJ/TMD -related training after completing graduate education. Conclusion. The results of the study show that dentists are not sufficiently familiar with the problems of TMD. 97.5% of the study participants consider it appropriate to conduct appropriate courses, seminars and lectures on disorders of the temporomandibular joints, which once again confirms the fact that continuing education is a necessity to ensure the proper level of training of specialists of all specialties, who are often primary care doctors in the diagnosis of TMD.